2023
DOI: 10.1126/sciadv.adi5019
|View full text |Cite
|
Sign up to set email alerts
|

Shifted sediment-transport regimes by climate change and amplified hydrological variability in cryosphere-fed rivers

Ting Zhang,
Dongfeng Li,
Amy E. East
et al.

Abstract: Climate change affects cryosphere-fed rivers and alters seasonal sediment dynamics, affecting cyclical fluvial material supply and year-round water-food-energy provisions to downstream communities. Here, we demonstrate seasonal sediment-transport regime shifts from the 1960s to 2000s in four cryosphere-fed rivers characterized by glacial, nival, pluvial, and mixed regimes, respectively. Spring sees a shift toward pluvial-dominated sediment transport due to less snowmelt and more erosive rainfall. Summer is cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
(102 reference statements)
1
5
0
Order By: Relevance
“…From May to October, the relationship between Q and SSC shows a clockwise variation (Figure 9a), with both variables increasing from spring, peaking in summer, and then declining. This pattern is consistent with findings from studies in other regions of the QTP plateau (Li, Overeem, et al, 2021; Zhang et al, 2023). However, at different event scales, when water–sediment variations are driven by individual events or several events simultaneously, there are differences in the SSC‐ Q variation curves.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…From May to October, the relationship between Q and SSC shows a clockwise variation (Figure 9a), with both variables increasing from spring, peaking in summer, and then declining. This pattern is consistent with findings from studies in other regions of the QTP plateau (Li, Overeem, et al, 2021; Zhang et al, 2023). However, at different event scales, when water–sediment variations are driven by individual events or several events simultaneously, there are differences in the SSC‐ Q variation curves.…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, autumn exhibits high Q but low SSC, resulting in a smaller increase in SSF compared with spring (Figures 9a and 3). Zhang found that an increase in summer rainstorm events leads to amplified variability in river Q and higher peaks in SSC during the summer season (Zhang et al, 2023). The occurrence of summer rainstorm events results in an inverted ‘V’‐shaped variation in both Q and SSC (Figure 5), leading to an overall increase in sediment concentration and discharge fluctuations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations